The Engineering Characteristics and Classifications of Rock Masses along Road Section from Prambanan to Patuk, Yogyakarta, Indonesia - Aisyah Shahirah Juhari; I Gde Budi Indrawan, Dr.; Wahyu Wilopo (Journal of Applied Geology, 2021)
Several attraction places and agriculture area that essentials for tourism and villager to do their activities are located approximately 6 km along the road of Candi Ijo to Ngoro-Oro in between Prambanan and Patuk sub-districts, Yogyakarta, Indonesia. Many jointed rock masses along the road have the potential to fail. This paper describes the rock mass characteristic and quality determined using the Geological Strength Index (GSI) and Rock Mass Rating (RMR) classifications. The rock mass characteristic and quality were essentially the preliminary results of a study to evaluate stability of the rock slopes along the road of Candi Ijo to Ngoro-Oro. Field observation and laboratory tests were carried out to determine parameters of the GSI and RMR.  The results show that the slopes in the study area consisted of tuffaceous sandstone, vitric tuff, lithic tuff, cemented tuffaceous sandstone, lapilli tuff, subarkose, laminated mudrock, and laminated tuffaceous sandstone. The intact rocks were classified as weak to very strong. The research area consisted of three rock mass qualities, namely fair rock mass quality having GSI between 30 and 45 and RMR between 41 and 60,  good rock mass quality having GSI between 46 to 65 and RMR between 61 and 80, and very good rock mass quality having GSI > 65 and RMR between 81-100. The relationship between GSI and RMR obtained in this study was in good agreement with that proposed by Hoek et al. (1995).